2006
DOI: 10.1016/j.amepre.2006.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Health Effects of Transport Interventions

Abstract: BackgroundThere is little evidence about the effects of environmental interventions on population levels of physical activity. Major transport projects may promote or discourage physical activity in the form of walking and cycling, but researching the health effects of such "natural experiments" in transport policy or infrastructure is challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 28 publications
0
65
0
4
Order By: Relevance
“…There are various methodological challenges in conducting prospective evaluations of environmental interventions and relocation studies, and some of the evaluations of changes to the environment have had methodological limitations [25,26]. Despite these challenges and limitations, in recent years some studies that examined the effects of changes to the environment have been published [27].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…There are various methodological challenges in conducting prospective evaluations of environmental interventions and relocation studies, and some of the evaluations of changes to the environment have had methodological limitations [25,26]. Despite these challenges and limitations, in recent years some studies that examined the effects of changes to the environment have been published [27].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…We summarised these issues into contrasting narratives and articulated them as two equally valid, competing, testable, overarching hypotheses about the effects of the intervention, expressed in the form of vignettes of two alternative extreme cases, a 'virtuous spiral' and a 'vicious spiral' ( Table 1). 52,53 An independent Public Local Inquiry (PLI) in 2003 considered the arguments for and against the construction project. The inquirers concluded that the claimed benefits were likely to be 'ephemeral' and that the new motorway 'would be very likely to have very serious undesirable results' for local communities, and, therefore, recommended against the proposal.…”
Section: The Extension Of the M74 Motorway In Glasgowmentioning
confidence: 99%
“…However, they are also important sources of methodological and other information to be used when planning new studies. Our own systematic reviews on the health effects of housing improvement and new road building directly informed the development of new primary studies assessing the outcomes of the provision of new social housing and the building of a new motorway, respectively (Ogilvie et al, 2006). The specific contribution of these reviews -aside from identifying the partial state of the evidence in these fields, and thus indicating the need for new research -was to help specify and refine the research questions, to identify the primary and secondary outcomes, and to estimate the possible range and size of positive and negative effects.…”
Section: What Are the Resource Implications?mentioning
confidence: 99%